THE LAWS PROTECTING CHILD WITNESS IN GIVING EVIDENCE: Harmonization Between Malaysian Laws and As-Shariah. - Mohamad Ismail Bin Mohamad Yunus; Nik Rahim Nik Wajis; Mualimin Mochammad Sahid; Nurliyana Shahira Baharli (Faculty of Law, Universitas Lampung, 2021)
Since issues of child abuse and other crimes against children have been brought to the public's attention through the media, this article considers to highlight one of the issues relating to the protection of child. The issue of the laws protecting child witnesses in giving evidence will come into the discussion. This paper considers the issue of corroboration of the child witness in the aspects of sworn and unsworn statements to determine whether the evidence given by children will be relevant and admissible in Courts. In tackling the issues, the research methodology applied by the authors is by analyzing and evaluating the decided cases and studying the substantive laws procedure in protecting child witnesses in giving testimony in Courts. The expectation findings of this paper are to harmonize between Malaysian and Islamic law relating to the protection of child witnesses in giving evidence in the court of law. After having observed the conflicts or the problems that had stem out of the current laws and procedures governing child witnesses as to the remedies, the final part of the article proposed some solutions and recommendations from the Islamic point of view.